The Impact of Using Interactive Whiteboard on Developing the Grammatical Competence of Iraqi EFL Learners (Journal of the College of Basic Education, 2022)
Grammar instruction is the most focal element in language teaching for EFL students and can be employed as a means of improving the foreign language learning. It raises students' understanding of major ideas in a text, exploring the text structure; it seems to be essential for good use of language. Researches have shown that different types of teaching strategies are suggested to improve the ability of learning grammatical rules. The Interactive Whiteboard is adopted in the present study as a teaching aid that can be used to facilitate communicative and meaningful learning. Therefore, this study aims to investigate the effect of employing Interactive Whiteboard in teaching grammar on developing Iraqi EFL learners’ grammatical competence. The null hypothesis states that there is no statistically significant difference between the mean scores of the students who are taught grammatical structures using the Interactive Whiteboard and that of the students who are taught these structures using the method recommended by the teacher’s book. The population of the present study is the female students of the fifth-grade (the scientific branch) preparatory schools in Baghdad during the academic year 2016-2017. The sample of the study involves 83 students. The experimental group consists of 42 students whereas the control group consists of 41. These two groups are randomly chosen from Baghdad Preparatory School for Girls in Baghdad. The subjects of both groups are equalized in the level of their parents’ education, their age, their achievement in English in the mid-year exam, their grades on the pre-test, as well as some extraneous factors. To fulfil the aim of the study, an experiment is conducted using a non-equivalent pretest posttest control group design. These groups are taught the same material, which contains three units from the textbook English for Iraq 5th preparatory (units 5, 6 and 7) except for the Interactive Whiteboard, which is introduced to the experimental group only. The researcher herself taught the two groups.